The Effectiveness Of Yoga Therapy And Exercise Therapy On Sleep Quality In Patients With Chronic Kidney Disease: A Systematic Review - Puteri Hirika Reptes; Yulia Yulia; Chiyar Edison; Sri Yona (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2026)
Sleep disturbances are highly prevalent among patients with Chronic Kidney Disease (CKD), occurring both in the pre-dialysis stage and among individuals undergoing hemodialysis or peritoneal dialysis. These disturbances can significantly impair overall quality of life. Various factors contribute to sleep disorders in CKD patients, including the accumulation of uremic toxins, pain, pruritus, dyspnea, anxiety, and the side effects associated with dialysis therapy itself. Physical activity-based interventions, such as aerobic exercise and yoga, have shown substantial potential in improving sleep quality. The objective of this systematic review is to evaluate the effects of yoga and aerobic exercise interventions on sleep quality in patients with CKD. A comprehensive literature search was conducted using databases including ProQuest, PubMed, Scopus, the International Journal of Health Sciences and Research, Springer, and the Iranian Journal of Nursing and Midwifery Research. Only full-text articles published in English between 2019 and 2024 were included. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Thirteen studies were identified: 11 Randomized Controlled Trials (RCTs), 1 quasi-experimental study, and 1 qualitative study. Analysis of the 11 RCTs revealed that various interventions—particularly yoga, aerobic exercise, and cognitive behavioral therapy (CBT) were employed to improve sleep quality. Among these, yoga and aerobic exercise were found to significantly enhance sleep quality in CKD patients, especially those undergoing hemodialysis, with aerobic exercise demonstrating more consistent benefits. Conversely, CBT did not produce significant improvements in sleep quality compared to the control group, though it did show limited effects on reducing depressive symptoms and dysfunctional beliefs. The quasi-experimental study examined the impact of yoga exercise and found it to be a contributing factor to improved quality of life, including better sleep. The qualitative study employed a phenomenological approach to explore the subjective experiences of CKD patients with fatigue caused by poor sleep, aligning with the study's aim of understanding this phenomenon from the patient’s perspective.